The Dissolution of the Monastic Houses in Iceland - Steinunn Kristjánsdóttir (Religions, 2024)
The founding of the fourteen monasteries that operated for varying lengths of time in Iceland are in most cases known, but their dissolution differs. It is, however, known that none of them were closed due to plagues, natural disasters, or economic crises but rather because of administrative reasons. Five of the monasteries perished within a few decades; however, most of them perished because of political disputes between secular and ecclesiastical powers in Iceland during the thirteenth century. On the other hand, nine of them became highly prosperous but were dissolved following the Lutheran Reformation in the mid-sixteenth century. The truth is that monasticism vanished in Iceland with the closure of the last one in 1551, and their previous occupation was thereby discontinued. Here, an attempt will be made to obtain an overview of their dissolution, but their growth and development were in all cases dependent on the country’s authorities at any given time, ecclesiastical and royal. Still, the circumstances of their dissolutions varied nonetheless between monasteries.